PROCESS PLANNING AND SCHEDULING WITH PPW DUE-DATE ASSIGNMENT USING HYBRID SEARCH - Demir, Halil Ibrahim; Cakar, Tarık; Ipek, Mumtaz; Erkayman, Burak; Canpolat, Kadriye (MATTER: International Journal of Science and Technology, 2016)
Although IPPS (Integrated Process Planning And Scheduling), and SWDDA (Scheduling With Due Date Assignment) are two popular area in which numerous work is done, IPPSDDA (Integrated Process Planning, Scheduling And Due Date Assignment) is a new research field only a few works are done. Most of the works assign common due dates for the jobs but this study assigns a unique due date for each job in a job shop environment. Three terms are used at the performance measure which is weighted tardiness, earliness, and due dates. Sum of all these terms is tried to be minimized. Different level of integration of these three functions is tested. Since job shop scheduling is alone NP-Hard, integrated solution is harder to solve that’s why hybrid search and random search are used as solution techniques. Integration found useful and as integration level, the increased solution is found better. Search results are compared with ordinary solutions and searches are found useful and hybrid search outperformed random search.